Vernacular budgeting and accounting routines : a longitudinal constructive case study - Mättö, Toni; Järvenpää, Marko; Peura, Pekka; Kangasjärvi, Merja; Lehtinen, Harri (Emerald, 2022)
Purpose This case study aims to report a longitudinal analysis of the development and use of local “vernacular” accounting practice and a digital rolling-forecast system known as TeamBudget in a public sector organization. Design/methodology/approach The study employs the constructive research approach which utilizes participative observation in the development of TeamBudget over the 15 years since 2004. The empirical data utilized includes eight interviews and documentary data for the system created. Findings The study demonstrates how the actions of employees responsible for developing a locally relevant financial planning system, TeamBudget, facilitated the emergence of new accounting routines associated with the newly created system. A locally created accounting system thus became institutionalized into a wider organizational setting over time. The current study presents findings that explain the routinization of informal accounting activities and the subsequent institutionalization process. Practical implications Understanding the potential influence of local action on the organization-wide accounting system may foster the creation of accounting tools that could spread participation and commitment throughout a public sector organization, contributing towards enhancing the enabling effect of an organizational accounting system. When designing a local budgeting system, decoupling it from the organizational system may promote its institutionalization. Originality/value Antecedents of informal accounting routines have received little research attention. This study illustrates actions relating to local accounting practice were antecedents of accounting routines and subsequent institutional changes in broader organizational practices in a public sector organization. The study demonstrates how vernacular accounting practice can facilitate the institutionalization process.
Keywords: Accounting routines; Case study; Constructive research approach; Institutionalization; Vernacular accounting; public sector; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|